Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1186/1471-2458-12-146
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and premature death in Estonian men: a study of forensic autopsies using novel biomarkers and proxy informants

Abstract: BackgroundAlcohol makes an important contribution to premature mortality in many countries in Eastern Europe, including Estonia. However, the full extent of its impact, and the mechanisms underlying it, are challenging issues to research. We describe the design and initial findings of a study aimed at investigating the association of alcohol with mortality in a large series of forensic autopsies of working-age men in Estonia.Methods1299 male deaths aged 25-54 years were subject to forensic autopsy in 2008-2009… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…It may be that people who consumed surrogate alcohol consumed more ethanol than those people who consumed beverage alcohol (i.e. more heavy drinking occasions resulting in a higher average consumption) (for the relationship between heavy drinking and surrogate consumption, see ), or that people who drank surrogate alcohol did so in a more detrimental pattern of irregular heavy drinking (for definitions see ; for the relationship between surrogate drinking in Russia and detrimental drinking patterns see ). Both regular and irregular heavy drinking have been linked to higher mortality and burden of disease .…”
Section: Resultsmentioning
confidence: 99%
“…It may be that people who consumed surrogate alcohol consumed more ethanol than those people who consumed beverage alcohol (i.e. more heavy drinking occasions resulting in a higher average consumption) (for the relationship between heavy drinking and surrogate consumption, see ), or that people who drank surrogate alcohol did so in a more detrimental pattern of irregular heavy drinking (for definitions see ; for the relationship between surrogate drinking in Russia and detrimental drinking patterns see ). Both regular and irregular heavy drinking have been linked to higher mortality and burden of disease .…”
Section: Resultsmentioning
confidence: 99%
“…Thus, although at autopsy the ethanol concentration is used commonly to determine whether acute intoxication is implicated as a cause of death, it is not informative about whether a death might be attributable to long-term harmful drinking. We have shown previously that at post-mortem GGT and EtG were the markers related most strongly to proxy-reported frequency of drinking [16]. Recently Rainio et al have shown that measuring vitreous humour EtG by immunoassay is a useful forensic tool for screening for ante-mortem alcohol use [25].…”
Section: Alcohol Biomarkersmentioning
confidence: 82%
“…The circumstances in which a forensic autopsy is performed in Estonia have been described previously 16. According to data from the Estonian Forensic Science Institute, about 90% of forensic autopsy cases are tested for alcohol and 35–40% of these have a blood ethanol concentration exceeding 0.5 mg/g.…”
Section: Discussionmentioning
confidence: 99%
“…The “other alcohol” group contains surrogate non-beverage alcohols (ethanol-containing liquids not intended for consumption), which are drunk particularly among men in Estonia [ 36 , 37 ]. In a previous study of association of alcohol with the mortality of Estonian men aged 25–54 years, alcohol was found in blood in concentrations ≥ 0.2 mg/g in 55% cases of death [ 38 ]. Results of that study of men also showed evidence of alcohol-induced pathologies in 75% of cases, and 32% had pathologies in two or more organs [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Ringmets et al. [ 38 ] it was stated that liver enzymes, used widely to detect liver damage in living subjects, have a limited postmortem value. AST and ALT are increased by haemolysis and hypoxia and so are subject to differences in the process of dying.…”
Section: Discussionmentioning
confidence: 99%